2024
DOI: 10.1111/joa.14067
|View full text |Cite
|
Sign up to set email alerts
|

Geometric growth of the normal human craniocervical junction from 0 to 18 years old

Juliette Raoul‐Duval,
Angèle Ganet,
Sandro Benichi
et al.

Abstract: The craniocervical junction (CCJ) forms the bridge between the skull and the spine, a highly mobile group of joints that allows the mobility of the head in every direction. The CCJ plays a major role in protecting the inferior brainstem (bulb) and spinal cord, therefore also requiring some stability. Children are subjected to multiple constitutive or acquired diseases involving the CCJ: primary bone diseases such as in FGFR‐related craniosynostoses or acquired conditions such as congenital torticollis, cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This may enable us to test the effect of muscle action, the mechanical properties of the soft tissues, and to test the relative importance of variation in the anatomy of the facets (and the degree of symmetry which may vary between individuals) as potential driver of mobility of the secondary movements. Finally, this type of simulation would also enable the estimation of the influence of the overall bone geometry (more specifically through growth, see Raoul-Duval et al, 2024) on primary motion through variation in insertion sites for tendons and ligaments, and therefore lever arms.…”
Section: Form-function Relationship In the Human Craniocervical Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…This may enable us to test the effect of muscle action, the mechanical properties of the soft tissues, and to test the relative importance of variation in the anatomy of the facets (and the degree of symmetry which may vary between individuals) as potential driver of mobility of the secondary movements. Finally, this type of simulation would also enable the estimation of the influence of the overall bone geometry (more specifically through growth, see Raoul-Duval et al, 2024) on primary motion through variation in insertion sites for tendons and ligaments, and therefore lever arms.…”
Section: Form-function Relationship In the Human Craniocervical Jointmentioning
confidence: 99%
“…In the case we found that kinematics can be inferred from morphological features, decision making and surgical planning would be greatly facilitated as the aimed functional outcome (mobility and stability) could be translated into a clear objective of morphological outcome. This is especially true since a recent study has paved the way for this investigation by providing a thorough quantitative description of the geometric growth of the CCJ from postnatal stage to 18 years old (Raoul-Duval et al, 2024).…”
mentioning
confidence: 99%